A comprehensive literature review on the oral microbiota: key concepts and implications for dental and systemic health - Asmae Benabderrahmane; Majid Atmani; Kaoutar Hamriri; Zoubida Laghrari; Saadia Belmalha (Novel Research in Microbiology Journal)
The oral microbiota plays a crucial role in maintaining oral health by forming a dynamic ecosystem across the buccal components. It contributes to oral homeostasis through pathogen defense, pH regulation, local immune support, biofilm formation, nutrient metabolism, and microbial balance preservation. Dental biofilms influence oral health by maintaining balance or contributing to conditions such as dental caries and periodontal diseases. Advancements in studying the oral microbiota have evolved from culture-dependent to culture-independent methods. Next-generation sequencing technologies such as Illumina platforms, have revolutionized the human understanding by revealing comprehensive microbial composition and functional insights. These methods collectively deepen our understanding of oral microbial communities, which are pivotal for maintaining both oral and systemic health. This review aims to explore dental caries, periodontal diseases, and other oral infections, detailing their symptoms, progression, and treatments. Dental caries manifests several symptoms from toothache to abscesses, managed through oral hygiene and restorative procedures. Periodontal diseases cause gum inflammation, necessitating plaque control, deep cleaning, and/ or surgery for resolution. Other infections, including canker sores, oral candidiasis, and herpes are discussed alongside their treatments such as topical agents, antifungals, and antivirals. Conventional treatments encompass antibiotics, antifungals, chlorhexidine, and invasive procedures, thus effectively eliminate pathogens and restore oral health.